Biocorrosion and biocompatibility of Zr–Cu–Fe–Al bulk metallic glasses. (18th October 2013) - Monfared, Amin; Vali, Hojatollah; Faghihi, Shahab
Abstract : Owing to their unique chemo‐physical and structural characteristics, amorphous bulk metallic glasses (BMGs) are of great demand for fabrication of variety of advanced and innovative products including surgical and biomedical tools and devices. In this study, a series of Ni‐free Zr‐based BMGs in Zr–Cu–Fe–Al system are fabricated using copper‐mold casting technique, and their biocorrosion and biocompatibility are evaluated with respect to their corrosion behavior in the phosphate buffered saline (pH = 7.4) solution. Anodic polarization curves, scanning electron microscopy combined with energy‐dispersive X‐ray, and wettability analyses are conducted to characterize the surfaces of BMG samples. The biocompatibility of the BMG and control samples is studied by comparing cell–substrate interactions among different samples. It is found that Zr60 Cu20 Fe10 Al10 displays a higher passive region compared with that of Zr60 Cu22.5 Fe7.5 Al10, but both BMGs exhibit lower corrosion resistance compared with Ti–6Al–4V alloy. By addition of titanium to Zr–Cu–Fe–Al system (Zr60 Ti6 Cu19 Fe5 Al10 ), a significant increase in the passive region of the polarization curve is detected. The cell culture experiments reveal that the number of attached and grown cells is significantly higher on the surface of the treated BMGs as compared with Ti–6Al–4V substrates and the culture plate as controls. There is no noticeable difference in cellular morphology among the BMG samples, and no cytotoxicity is detected. We speculate that the interaction of water molecules and matrix proteins with the surfaces of BMGs plays an important role in cell–substrate interactions and improved cell response. Copyright © 2013 John Wiley & Sons, Ltd.